Development of 2D Animation Learning Video Media for the TAPPS Learning Model to reduce Mathematics Phobia - Novianti Novianti; Siti Khaulah; T Rafli Abdillah (Postgraduate, University of Mataram, 2023)
2D animated video media emerges as a viable remedy aimed at enhancing student learning outcomes and the effective implementation of the Thinking Aloud Pair Problem Solving (TAPPS) pedagogical approach. The approach adopted involves the utilization of the ADDIE methodology to guide the development of meticulously designed media, a design that has undergone comprehensive validation by multiple assessors, encompassing both content and media scrutiny. This assessment has been conducted across various evaluation criteria. The data collection methodology employed encompassed tests and questionnaires to gauge student reactions. As evidenced by the material validation phase, the average percentage achieved was 77.13%, falling within the